Managing Indonesian Head of Local Government Elections During the COVID-19 Pandemic Period - Perdana, Aditya (Jurnal Politik, 2021)
This paper analyses the Local Government elections (Pilkada) in Indonesia during the COVID-19 pandemic in relation to its postponement by looking at three critical aspects in the electoral management framework decision-making process, service outputs, and service outcomes framed. Some findings of this paper are: first, decision making for conducting the Pilkada 2020 was politically uneasy; second, good quality of service outputs from Pilkada 2020 was signed by convenience dimension which can be captured by voter compliance on health protocols in the polling station; third, the best evaluation for service outcomes is coming from the high percentage of voters turn out that need to explore more on that phenomena.